FLUJO DE FONDOS: PODEROSA HERRAMIENTA DE GESTIÓN EN LOS NEGOCIOS (Parte I) - Porlles Loarte, José (2005)
One demonstrates difficulties in the use of the state of movement of bottoms, in the measurement that in varied Literature does not clarify with the forcefulness of the case the existence of three approaches of definition of bottoms that are adopted based on the objective that is persecuted in the analysis. This situation leads to that this state is less included/ understood and therefore its effective use in the financial decisions has not been amplified. Considering which the methodologic tools establish a sequence of action guidelines to confront a certain kind of problems, the present work has this context with the purpose of improving of integral way the quality in the analysis and interpretation of the movement of bottoms in its different versions to determine the significant changes in a determined period of the management. In this first part settles down the conceptual frame of the flow of bottoms for its exact understanding and use like a solid tool of management.